Insulin sensitivity and blood glucose level of sepsis patients in the intensive care unit - M. Suhaimi, Fatanah; Jamaludin, Ummu K.; Abdul Razak, Normy Norfiza; Mat Nor, Mohd Basri; Md Ralib, Azrina; Wan Muhd Shukeri, Wan Fadzlina; Hasan, Mohd Shahnaz; Abu-Samah, Asma; Azman, Nizuwan (Institute of Electrical and Electronics Engineers Inc., 2019)
Sepsis and hyperglycemia are highly associated with increases in mortality rates, particularly in the critically ill patients. Sepsis diagnosis has been proven challenging due to delay in getting the blood culture results. Thus, often clinical experiences overrule the protocol to prevent the worsening outcome of the patients. In some cases, the erroneous clinical judgement cause antibiotic resistance and even adverse clinical outcomes. This paper investigates the correlation between two parameters; insulin sensitivity and blood glucose level among sepsis patients. The blood glucose level is measured at the bedside during the patient's stay, whereas insulin sensitivity is obtained using the validated glucose-insulin model. Thus, the insulin sensitivity is a specific parameter of the patient, unregimented of the protocol given to the patient. The same parameters, blood glucose and insulin sensitivity, are also compared to the non-sepsis patients to establish a relationship that can be used for sepsis diagnosis. Given the availability of these two parameters that can be captured rapidly and instantly, a significant relationship can, therefore, help clinicians to identify sepsis at an early stage without second-guessing.